Various methods of financing students' education comply with Islamic law (Journal of Economic Additions, 2019)
Families are struggling to find funding to support the university education of their children, where some of them have to sell their property for this purpose. This study aims at presenting a set of methods that can be applied in Islamic societies and contribute to solving this problem. These methods include educational savings fund, educational endowment, student sponsorship, and student loans. Some of these methods are applied in Islamic countries and will be covered in the study in brief. The study also includes proposals for the development of education loans granted by some Islamic banks to be more effective in solving this problem.Keywords: Islamic Financing; Education; Students; Loan; utilitiesJel Classification Codes: XN1, XN2.